If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 0.02(y + -3) + 0.14 = 0.04y + -0.03(30) Reorder the terms: 0.02(-3 + y) + 0.14 = 0.04y + -0.03(30) (-3 * 0.02 + y * 0.02) + 0.14 = 0.04y + -0.03(30) (-0.06 + 0.02y) + 0.14 = 0.04y + -0.03(30) Reorder the terms: -0.06 + 0.14 + 0.02y = 0.04y + -0.03(30) Combine like terms: -0.06 + 0.14 = 0.08 0.08 + 0.02y = 0.04y + -0.03(30) Multiply -0.03 * 30 0.08 + 0.02y = 0.04y + -0.9 Reorder the terms: 0.08 + 0.02y = -0.9 + 0.04y Solving 0.08 + 0.02y = -0.9 + 0.04y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-0.04y' to each side of the equation. 0.08 + 0.02y + -0.04y = -0.9 + 0.04y + -0.04y Combine like terms: 0.02y + -0.04y = -0.02y 0.08 + -0.02y = -0.9 + 0.04y + -0.04y Combine like terms: 0.04y + -0.04y = 0.00 0.08 + -0.02y = -0.9 + 0.00 0.08 + -0.02y = -0.9 Add '-0.08' to each side of the equation. 0.08 + -0.08 + -0.02y = -0.9 + -0.08 Combine like terms: 0.08 + -0.08 = 0.00 0.00 + -0.02y = -0.9 + -0.08 -0.02y = -0.9 + -0.08 Combine like terms: -0.9 + -0.08 = -0.98 -0.02y = -0.98 Divide each side by '-0.02'. y = 49 Simplifying y = 49
| 4a^2+24a+36=0 | | 3*-12=36 | | 0.2x+7.2=5.9 | | (x+1)(x-1)=5(x+1) | | 5x-4(-x+8)=-31 | | 5x^2-x-54=0 | | 0.02(y-4)+0.14y=0.04y-0.03(30) | | 29-5x=4+7x | | 2*(x^2)+3*x-2000=0 | | x/6-4=16 | | 5x-x-54=0 | | 6(x-6)+6=3(x-7) | | (x-3)(2x+3)=5 | | -6(0.1x+0.4)-1.3=-0.1 | | 5x^2+13x-1= | | -3+7(x-1)=12x+2-5x | | 4x+6=42-2x | | 1-7=x-x | | .58y-.25=2y-1.7 | | -2(2x-1)+7=-4x+9 | | -8x+15=-10x+5 | | n-7=3 | | 7x-3(6-x)=16 | | 4x-1=-2x+11 | | 41=16-6-x | | n-4=20 | | 4z-1=2x+11 | | -4(x+5)-6=-26 | | (1/2)x+4=x-4 | | (12+15)(56)= | | n+20=37 | | (4-6i)(4+8i)= |